Analysing Hawk-Eye ball-tracking data to explore successful serving and returning strategies at Wimbledon - Fitzpatrick, A.; Stone, J. A.; Choppin, S.; Kelley, J. (International Journal of Performance Analysis in Sport, 2024)
Investigations of elite tennis match-play have highlighted the importance of serving and returning strategies. This study establishes the most common and effective strategies used by male and female players at Wimbledon, and identifies associated winner-loser differences. Hawk-Eye ball-tracking data from 302 men`s and 139 women`s singles matches contested between 2016 and 2018 were analysed using confidence intervals, Chi-square and Chi-square partitions. For both sexes, first serves to lateral areas (Zones A and D) of the service boxes were more common and more successful than first serves to central areas (Zones B and C). Second serves to lateral areas also tended to be more successful than those to central areas, but players typically prioritised safety, often executing second serves to Zone C (central, but towards the backhand of right-handed opponents). Men and women hit more serve-returns to central areas than lateral areas of the court, despite serve-returns to lateral areas being more successful. Furthermore, winning male players were more accurate than losing male players, executing a comparatively higher percentage of serves and returns to lateral areas; winning female players demonstrated this on first serves only. These findings can be used to improve the specificity and representativeness of players` grass court training.